Danto and pluralism in contemporary art and art criticism - Domínguez Hernández, Javier (Estudios de Filosofía, 2008)
A. C. Danto's approaches to pluralism in contemporary art and art criticism take as a point of reference the eighties, a short period in which pluralism emerged as a theme for artistic consciousness. Artistic movements of the sixties such as pop, minimalism, fluxus, had abolished aesthetics as a criterion for defining art: a work of art could be anything. This could no longer be assimilated by criticism but by the philosophy of art, the only one capable of a concept of transhistoric and pluralist art in itself. However, pluralism in art also requires criticism. The article exposes the difference between art philosophy and art criticism, and to face the challenge of pluralism, the difference between free art criticism and criticism dependent on the institutionalized art world. Finally, the article takes advantage of an allusion by Danto to associate the spirit of pluralism in art and politics.